2017
DOI: 10.1039/c7cp00023e
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the oxidative power of free iron–sulfur clusters

Abstract: The gas-phase reactions between a series of di-iron sulfur clusters FeS (x = 1-3) and the small alkenes CH, CH, and CH have been investigated by means of Fourier-transform ion-cyclotron resonance mass spectrometry. For all studied alkenes, the reaction efficiency is found to increase in the order FeS < FeS < FeS. In particular, FeS and FeS only form simple association products, whereas the sulfur-rich FeS is able to dehydrogenate propene and 2-butene via desulfurization of the cluster and formation of HS. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…[15][16][17][18][19] Reactions of small cationic iron sulfide clusters with small alkanes elucidated the oxidative power of these compounds. 20 Also molybdenum chalcogenide cations were investigated with gas-phase techniques. 21 Jarrold, Raghavachari and co-workers have focused on molybdenum oxide and sulphide cluster reactivity, [22][23][24][25][26] with studies involving H 2 and H 2 O bearing relevance for HER catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19] Reactions of small cationic iron sulfide clusters with small alkanes elucidated the oxidative power of these compounds. 20 Also molybdenum chalcogenide cations were investigated with gas-phase techniques. 21 Jarrold, Raghavachari and co-workers have focused on molybdenum oxide and sulphide cluster reactivity, [22][23][24][25][26] with studies involving H 2 and H 2 O bearing relevance for HER catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Gas-phase studies offer the advantage of dealing with well-defined and controllable systems. Such investigations give conceptual insight into the structure and behavior of individual molecules or small clusters as a model system for heterogeneous catalysis. Lang, Zhou, and Schwarz managed to obtain Fe 2 S x + ( x = 1–3) clusters and reacted them with small alkanes, which provided insight into the oxidative power of these species. Earlier, molybdenum chalcogenide cations were investigated in the Schwarz group .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that photoreactions of iron oxides have potential to impact the transformation of VOCs in the atmosphere. , Therefore, the chemical process of isoprene on iron oxide particles will be quite interesting, and it is very beneficial for atmospheric chemistry models to obtain the mechanistic insights. The surfaces of particles are complex, while gas-phase atomic clusters are considered as ideal models of active sites on related solid surfaces. Nanosized atomic clusters are of great importance to bridge atoms and their bulk counterpart. …”
Section: Introductionmentioning
confidence: 99%